Dificulties In Mathematics I Of The Pmma College Of Marine Engineering Fourth Class Midshipmen - Jackson C. Talosig (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The main objective of this study was to identify the difficulties encountered in Mathematics 1 of Fourth Grade Midshipmen/Females of the Philippine Marine Academy of Merchant College of Engineering. The difficulties encountered in Mathematics 1 include algebraic expressions, algebraic fractions, exponents and roots, linear, equations, and systems of linear equations. In addition, this study identified the factors that influence the respondents' difficulties with the topic. Respondents consisted of 50 students enrolled in the 2013-2014 academic year. The finding of this study is that there is a significant relationship between student respondents' performance in exams and their perceptions of the factors that lead to difficulties in Mathematics.